What Should Macroeconomists Know About Health Care Policy : A Primer - Hsiao, William (Washington, D.C. : International Monetary Fund, 2000)
This primer aims to provide IMF macroeconomists with the essential information they need in situations where they must address issues concerning health sector policy and when they have significant macroeconomic implications. Such issues can also affect equity and growth and are fundamental to any strategy of poverty reduction. The primer highlights the appropriate roles for the state and market in health care financing and provision. It also suggests the situations in which macroeconomists should engage health sector specialists in policy formulation exercises. Finally, it illustrates the different health policy issues that confront countries at alternative stages of economic development and the range of appropriate policy options.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet